(untitled) (Feni University Journal, 2026)
Automobile vehicles, a vital component of the urban environment, are also the main contributory factor of urban sound pollution. It is one of Sylhet zone’s most significant contributors to noise pollution. Sylhet is one of the most Bangladeshi cities with the speediest growth. The amount of transportation facilities (the number of automobiles) is growing along with population growth. In Sylhet city, noise pollution has been rising alarmingly. Noise refers to sounds that occur around us but are not a part of the environment under study. For this reason, during working days, between 6 am and 12 am, noise levels were supervised at 10 major places (Industrial Zone and Commercial Zone) throughout the city. The paper focused on the consequences of sound in the industrial and commercial zones of Sylhet City based on vehicular sound impact. The basic method of counting traffic was automatic recording. In addition, a sound level meter was used to record the sound volume at intervals of three hours. Implementing the passenger car unit (PCU) conversion factor, the data were calculated based on the 60-minute average of vehicle movements that crossed the location. “Environmental Conservation Rules-1997” was regarded as fundamental to analyzing the data. The sound level was higher than the allowed noise standard in all the selected industrial and commercial locations. It also demonstrated the influence of traffic clatter. Most of the time, the sound level at each site stayed persistently higher than the allowed range, and vehicular activity played a substantial role in each case. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (31-42)